Sexual minority status and psychotic symptoms: findings from the Netherlands Mental Health Survey and Incidence Studies (NEMESIS). Issue 2 (January 2014) - Gevonden, M. J.; Selten, J. P.; Myin-Germeys, I.; de Graaf, R.; ten Have, M.; van Dorsselaer, S.; van Os, J.; Veling, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Ethnic minority position is associated with increased risk for psychotic outcomes, which may be mediated by experiences of social exclusion, defeat and discrimination. Sexual minorities are subject to similar stressors. The aim of this study is to examine whether sexual minorities are at increased risk for psychotic symptoms and to explore mediating pathways. Method A cross-sectional survey was performed assessing cumulative incidence of psychotic symptoms with the Composite International Diagnostic Interview in two separate random general population samples (NEMESIS-1 and NEMESIS-2). Participants were sexually active and aged 18–64 years (n = 5927, n = 5308). Being lesbian, gay or bisexual (LGB) was defined as having sexual relations with at least one same-sex partner during the past year. Lifetime experience of any psychotic symptom was analysed using logistic regression, adjusted for gender, educational level, urbanicity, foreign-born parents, living without a partner, cannabis use and other drug use. Results The rate of any psychotic symptom was elevated in the LGB population as compared with the heterosexual population both in NEMESIS-1 [odds ratio (OR) 2.56, 95% confidence interval (CI) 1.71–3.84] and NEMESIS-2 (OR 2.30, 95% CI 1.42–3.71). Childhood trauma, bullying and experience of discrimination partly mediated the association. Conclusions The finding that LGB orientation is associated with psychotic symptoms adds to the growing body of literature linking minority status with psychosis and other mental health problems, and suggests that exposure to minority stress represents an important mechanism.